Participation patterns in talent development in youth sports - Güllich, Arne; Barth, Michael; Hambrick, David Z.; Macnamara, Brooke N. (Frontiers in Sports and Active Living, 2023)
There has been a longstanding debate about the question: What amounts of what types of youth sport activities optimally facilitate later athletic excellence? This article provides a review of relevant research. We first evaluate popular conceptualizations of participation patterns—early specialization, deliberate practice, and deliberate play. Then, we review the available evidence on associations between performance and individual participation variables. The review reveals conceptual, definitional, and empirical flaws of the conceptions of early specialization, deliberate practice, and deliberate play. These approaches thus possess limited usefulness for empirical research. A review of studies considering individual, clearly defined participation variables provides a differentiated pattern of findings: Predictors of rapid junior performance and of long-term senior performance are opposite. Higher-performing juniors, compared to lower-performing peers, started playing their main sport, began involvement in talent promotion programs, and reached developmental performance milestones at younger ages, while accumulating larger amounts of coach-led main-sport practice, but less other-sports practice. In contrast, senior world-class athletes, compared to less-accomplished national-class peers, started playing their main sport, began involvement in talent promotion programs, and achieved performance milestones at older ages, while accumulating less coach-led main-sport practice, but more other-sports practice. We discuss implications for theory, practice, and future research.